Land trades: Three novels about the work: Juan Martini, Sergio Chejfec and Hernán Ronsino - Korn, Guillermo (Tropelías: Review of Literary Theory and Comparative Literature, 2018)
The article proposes to investigate three novels of contemporary Argentine literature with a double question: how they represent the work and what territory built for their fiction? From there, we read critically, in the fold of those three way of writings –Martini, Chejfec and Ronsino–, different reflections that brought about the language and memory.